Relevance theory - Clark, Billy (Cambridge University Press, 2013)
The book is divided into two parts â€“ the first providing an overview of the essential machinery of the theory, and the second exploring how the original theory has been extended, applied and critically discussed. Clark offers a systematic framework for understanding the theory from the basics up, building a complete picture and providing the basis for advanced research across a range of topics. With this book, students will understand the fundamentals of relevance theory, its origins in the work of Grice, the relationship it has to other approaches, and its place within recent developments and debates; Includes bibliographical references and index; NV Ngôn ngữ học đối chiếu